2022
DOI: 10.3389/fpsyg.2022.1019984
|View full text |Cite
|
Sign up to set email alerts
|

Delving into the relationship between teacher emotion regulation, self-efficacy, engagement, and anger: A focus on English as a foreign language teachers

Abstract: Due to the potent role of teachers’ emotion regulation in effective teaching, it seems essential to see how emotion regulation can contribute to other relevant teaching constructs. In this regard, the present study is intended to probe into the causal relationship among teacher emotion regulation, self-efficacy beliefs, engagement, and anger. In so doing, the Language Teacher Emotion Regulation Inventory (LTERI), The Teacher Sense of Efficacy Scale (TSES), The Engaged Teacher Scale (ETS), and The Teacher Anger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 96 publications
3
33
0
Order By: Relevance
“…Likewise, Li et al (2018) concluded that enjoyment and anxiety are dominant in the language classroom and influence the in-class and final products of the learners. It is shown in the literature that teacher-student intercommunications play an important part in promoting LE in the classroom (e.g., Deng et al, 2022;Elahi Shirvan et al, 2020;Elahi Shirvan & Taherian, 2020). Class enjoyment is also inspired by the balance between context-oriented attributes and learners' mental necessities (Chen et al, 2021).…”
Section: Learner Enjoyment (Le)mentioning
confidence: 99%
“…Likewise, Li et al (2018) concluded that enjoyment and anxiety are dominant in the language classroom and influence the in-class and final products of the learners. It is shown in the literature that teacher-student intercommunications play an important part in promoting LE in the classroom (e.g., Deng et al, 2022;Elahi Shirvan et al, 2020;Elahi Shirvan & Taherian, 2020). Class enjoyment is also inspired by the balance between context-oriented attributes and learners' mental necessities (Chen et al, 2021).…”
Section: Learner Enjoyment (Le)mentioning
confidence: 99%
“…Furthermore, it was found that the participants’ immunity was a strong predictor of their ER. Finally, Deng et al ( 2022 ) conducted a study to reveal if EFL teachers’ ER was significantly correlated with their WE, self-efficacy, and anger. They discovered that the participants’ ER was positively correlated with their WE and self-efficacy and negatively linked with their anger at the workplace.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, empirical research has revealed a concerning negative relationship between System-Induced Educator Anger (AN) and the overall well-being of educators, indicating that such systemic-induced emotions can have detrimental effects on their mental health [12] . Furthermore, In the context of English as a Foreign Language (EFL) teaching, especially during the challenging period of the COVID-19 pandemic, studies have found a negative correlation between educators' ability to regulate emotions and the anger they experience due to systemic factors [13] . This suggests that external pressures from the educational system exacerbate emotional challenges for teachers.…”
Section: Literature Review 11 Research Model and Hypothesesmentioning
confidence: 99%